PENINGKATAN KEMAMPUAN LITERASI SAINS SISWA MELALUI PEMBELAJARAN BERBASIS DISCOVERY LEARNING SMA NEGERI 15 MAKASSAR - Taufiq, A. Muhammad Haerul; Ismail; Faisal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of the 21st century is becoming increasingly complex in the fields of knowledge, technology, and information on a global scale, fundamentally aimed at improving the quality of life for society. The type of this research is quasi-experimental. (Quasi Experiment). This research aims to determine how the literacy improvement of high school students in classes taught using the discovery learning model and classes taught using the conventional model, as well as to understand the impact of the discovery learning model on the literacy improvement of high school students. The design of this research is a pretest-posttest control group design. The population of this study consists of students from the XII MIPA class at SMAN 15 Makassar. The research samples are the XII MIPA 1 and XII MIPA 2 classes. The research instrument in this study is a science literacy ability test in the form of 20 multiple-choice questions. The data were analyzed using descriptive statistics, inferential statistics including normality tests, homogeneity tests, and hypothesis tests in the form of t-tests. The analysis of students' science literacy who applied the discovery learning model was better compared to the class that applied the direct instruction model. This is evidenced by the average science literacy score of the experimental class being 65.56 and the control class being 60.69, with the science literacy in the experimental class showing an increase based on the average N-Gain score of 44.55, categorized as moderate.